"You Teach What?" Black Males, New Latino South Classrooms, and Wanderlust. Issue 2 (3rd April 2021) - Salas, Spencer; Lewis, Chance W.; Siefert, Bobbi
ABSTRACT: An abundant and longstanding body of scholarship has underscored the White femininity of the U.S. K-12 teaching workforce and the need to diversify its ranks. Black males, in particular, potentially struggle with the notion of becoming teachers given their often highly negative lived experiences with schools and schooling including low expectations, racial stereotypes, microagressions, and disproportionate discipline and punishment. For those Black males who do enter teaching, they are often recruited as role models or "Otherfathers" to Black boys – expected to police first and teach second. However, relatively little has been said about Black males' choices to work with transnational children of immigration – especially in the context of the New Latino South. Theorizing an in-depth qualitative interview series through a Vygotskian framework of lived experiences/vivencias, in this article we narrate how Roman Fitzgerald (a pseudonym) came to be an ESOL Department Chair in the same mega-urban school district he had attended. Our findings point to socially constructed limitations that Black males face as they navigate graduate level teacher licensure programs and the profession – and their consequences for Black male teacher recruitment and retention in urban school contexts.